EFISIENSI FAKTOR-FAKTOR PRODUKSI USAHA PEMBESARAN IKAN NILA DALAM KARAMBA JARING APUNG DI KABUPATEN BANJAR - Yarna Hasiani (Universitas Lambung Mangkurat, 2015)
This study aims to (1) determine the efficiency of the price of the factors of production are allocated to the business floating net nila fish; and (2) comparing the economic efficiency of enterprises nila fish floating net between large business scale and small-scale enterprises. Efficient allocation of production factors to the overall price is not efficient. Efficiency has not been reached on the allocation of seed input and the outpouring of labor, which is the input for the second allocation should be increased so that the allocation can be optimized. Technically, there is a difference between the input allocation efficiency of business karamba jaring large scale tilapia fish floating on a small scale, on a scale where small businesses can allocate an optimal feed input rather than large-scale enterprises. Thus, this means that small-scale economically more efficient than large-scale enterprises.